Intelligent Logistics for Intelligent Production Systems - Martin Krajcovic; Patrik Grznar; Miroslav Fusko; Radovan Skokan (Communications - Scientific letters of the University of Zilina, 2018)
The main topic of the submitted paper is intelligent logistics and its integration into production systems. In the beginning, the problem that lies in the inadequate knowledge of the internal state has been defined. The new society-wide trends that will originate in a few years are also outlined. Those trends will affect factories and their logistics systems on a large scale. Therefore, it is necessary to have a strategy that takes these new trends into consideration. In this manuscript, is described a strategy for intelligent production systems, as well as technologies for different types of production-logistic strategies. Many of these technologies can be applied together with the Digital Twin. The Digital Twin is a new concept in the field of designing production and logistics systems in the factory. Finally, we provide a description of the implementation of the Digital Twin into the production and logistics system.